[¹²³I]FP‐CIT SPECT (DaTSCAN) may be a useful tool to differentiate between Parkinson's disease and vascular or drug‐induced parkinsonisms: a meta‐analysis. (30th April 2014) - Brigo, F.; Matinella, A.; Erro, R.; Tinazzi, M.
<x xml:space="preserve">Abstract</x> Background and purpose Differentiating idiopathic Parkinson's disease from secondary parkinsonian syndromes is crucial since their management and prognosis differ considerably. Functional imaging of the dopaminergic pathway by means of [¹²³I]FP‐CIT SPECT (DaTSCAN) might be useful in this regard, but its role is still controversial. The accuracy of DaTSCAN in the differential diagnosis between Parkinson's disease and vascular or drug‐induced parkinsonism was therefore systematically reviewed. Methods MEDLINE and CENTRAL were searched for studies aiming to determine accuracy measures (sensitivity, specificity, diagnostic odds ratio, positive and negative likelihood ratios) of DaTSCAN in differentiating between Parkinson's disease and vascular or drug‐induced parkinsonism. Results Five studies were included. Pooled accuracy measures in differentiating between Parkinson's disease and vascular or drug‐induced parkinsonism were relatively high, with sensitivity and specificity values above 85% and 80%, respectively. Conclusions DaTSCAN might accurately differentiate between early Parkinson's disease and secondary parkinsonian conditions, namely vascular or drug‐induced, in patients with clinically unclear parkinsonism. However, all the studies reviewed here show several methodological limits, which prevent definitive conclusions on the role of DaTSCAN being drawn in this context. Further studies are needed to confirm our results and definitely evaluate the utility of DaTSCAN in differentiating between Parkinson's disease and vascular or drug‐induced parkinsonism.